Thermal and Mechanical Characteristics of Unsaturated Polyester and Epoxy Blend - Abed, Doaa J.; H. Mahdi, Shatha; Akbar, Demiral (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Epoxy resin and a mixture with unsaturated polyester resin (UPE) were prepared as the matrix materials. The preparation technique included preparing circular and square molds with different weight ratios. Standard samples (40 mm diameter) were prepared for thermal conductivity tests. The results of the thermal conductivity test of the mixture showed that it decreased from (0.014) to (0.013) significantly, which helps in thermal insulation. The decrease in its thermal conductivity means that the structure of the base material is irregular. Hardness test was performed on samples made of epoxy resin with unsaturated polyester resin, and the best hardness reading was (64.5), but when replacing the unsaturated polyester resin with a higher percentage of epoxy resin, the ratio was (30.6), so the value (30.6) is the best hardness value. The test results show that the highest hardness value is (64.5), as for the results of the differential scanning calorimetry measurement. From these curves, it is clear that the value of the glass transition temperature increases from 50 to 179, and the value of the glass transition temperature decreases from 171 to 145.